IN VITRO ANTIMALARIAL ACTIVITY OF LEAVE PETROLEUM ETHER EXTRACT OF FICUS SYCOMORUS PLANT - Garga, M. A.; Ibrahim, M. K.; Mohammad, A.; Abdullahi, H. A.; Yusuf, M. B.; Ibrahim, N.; Garba, I. L.; Bako, I.; Salisu, B. (International Journal of Research -GRANTHAALAYAH, 2021)
In vitro anti-malarial activity of petroleum ether extracts of Ficus sycomorus leaves was investigated using Candle Jar method. The extractions were carried out through activity guided fractionation. Petroleum ether extract has the highest activity, at the concentration of 1mg and 0.5mg with percentage growth inhibition of (33.12 and 31.9%) respectively. These results suggest that the leaves of Ficus sycomorus plant have significant antimalarial activity and that the antiplasmodial agents might be as a result of the extract fractionated using the petroleum.